Effects of Ultrasound Application on the Improvement of Probiotic Properties and Antioxidant Activity of Kluyveromyces marxianus, Saccharomyces cerevisiae var. boulardii and Saccharomyces cerevisiae - Hamza Goktas; Demet Turali; Cansu Agan; Osman Sagdic (Turkish Journal of Agriculture: Food Science and Technology)
The objective of this study was to ascertain the impact of ultrasound application on the probiotic characteristics and antioxidant activity of yeasts. In this context, the pH changes, probiotic properties and antioxidant activities of K. marxianus (Km), S. boulardii (Sb) and S. cerevisiae (Sc) were determined by ultrasound application at different durations (5, 15, 30 and 60 minutes at 24 kHz). The lowest pH values were determined for cultures of Km (ultrasound non-applied K. marxianus), Sb-30 (30 min. ultrasound applied S. boulardii) and Sc-5 (5 min. ultrasound applied S. cerevisiae) as 4.48, 5.15 and 5.26, respectively. The hydrophobicity values of the yeast strains varied between 6% and 24%, increased with ultrasound application. Although S. boulardii had the highest tolerance to low pH and bile salts, the resistance of all yeast to low pH and bile salts decreased with ultrasound application. K. marxianus had the least survival under in vitro conditions, but ultrasound application increased survival of K. marxianus strains and slightly affected the survival rate of S. boulardii and S. cerevisiae. Increasing of duration time of ultrasound application resulted higher antioxidant activity and so the highest antioxidant activity was determined for Sb-60. Finally, ultrasound application could be used for the development of hydrophobicity and antioxidant properties of yeast cultures.